Estratégias para conservação de acessos de coqueiro anão do BAG da Embrapa Tabuleiros Costeiros - Machado, Caroline de Araújo (2012)
The conservation of the coconut palm has been investigated in recent years by research organizations, public and private. These studies have concentrated on obtaining conservation protocols in vitro using slow growth and cryopreservation. Storage as a means of maintaining the viability of pollen, it is important for the preservation of genetic variability, facilitates the exchange of germplasm and contributes greatly to the generation of variability obtained from artificial crosses increasing the efficiency of breeding programs. The objective of this work was to study the effect of mannitol and abscisic acid (ABA) on growth of seedlings of coconut dwarf accessions for conservation purposes, and in vivo studies of the viability and storage conditions of pollen grains. For the study of conservation by slow growth were used mature zygotic embryos of Gramame Red Dwarf (AVG) and Malayan Yellow Dwarf (AAM). The coconut embryos were inoculated in culture medium Y3 (Eeuwens, 1976) supplemented with 30 g L-1 sucrose, gelled with 0.7% agar in presence of 2.5 g L-1 of activated charcoal. Were tested the following concentrations of mannitol: 0; 0.1; 0.2, 0.3 and 0.4 M. In other experiment was tested the following ABA concentrations: 0, 10, 20, 30 and 40 mM. The 0.1 and 0.2 M mannitol reduced the plantlets length of AAM and AVG accessions, respectively at 180 and 270 days of cultivation. Concentrations above 20 μM ABA were viable to inhibit the plantlets growth to 180 and 270 days. The ABA concentrations tested not inhibit the access AVG growth. For the study of determining the culture medium in germination of pollen grains, it was evaluated four culture media: Brewbaker and Kwack (1983) modified by Sousa et al. (2010); Lora et al. (2006); Sousa et al. (1998) and Sousa et al. (1998) modified by the author, in different times: 0, 24, 48 and 72 hours. The Lora culture medium promoted the major in vitro germination of AVeJBr pollen grains. Pollen grains of AVeJBr access showed viability up to 72 hours (3 days). The condition of storage at -20°C and -80°C promotes more viable pollen germination of AVC access up to 60 days. The condition of storage at -196°C promotes greater availability of pollen germination by AVeJBr access up to 60 days.